Alcohol use, antiretroviral medication adherence and Sexual behaviors among young HIV-Infected Women engaged in HIV Medical Care in St. Petersburg, Russia - Olga S Levina; Jennifer L Brown; Jessica M Sales; Eve S Rose; Polina Safonova; Nickolay A Belyakov; Vadim V Rassokhin; Ralph J DiClemente (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2017)
With over a million people diagnosed with HIV by the beginning of 2016, Russia has one of the world's most rapidly developing HIV epidemics. Evidence suggests young women in Russia are at high risk for HIV  and comprise a substantial portion of newly infected people. Our study is one of the first to explore via qualitative interviews among young Russian women in HIV care in St. Petersburg (N=30) the role of alcohol use in their HIV treatment adherence and sexual behaviors. Our study reveals that alcohol misuse among Russian women being treated for HIV may be under reported and misinterpreted. Findings emphasize the role of biographic and socio-environmental factors and differences in how alcohol fuels potentially risky and harmful health behaviors among young HIV-infected women under treatment. Programs designed with the focus on individual variations in the difficulties women face in reducing their alcohol use that are gender- and culturally-congruent in Russia are urgently needed.